The Interface Between the Written and the Oral in lfa Corpus - Omotade Adegbindin (Yoruba Studies Review, 2021)
While the modernists in the field of African philosophy embrace writing as a precondition for philosophy and forcefully maintain the need to cast philosophy in the image of science, the traditionalists insist that African philosophy is essentially a philosophical reflection on African oral traditions, morals, and religious practices. This essay argues that the intransigent relationship between the modernists and the traditionalists persists because the two dominant schools have failed to recognize the need to furnish a paradigm of interaction between their projects. From the standpoint of lfa, therefore, this paper rejects the written-oral dichotomy that is central to both the modernist and the traditionalist orientations, occasioned by their parochial and provincial conceptions of philosophy respectively. The paper shows how lfa as a complete philosophy puts a premium on the need to bring individual views in oral and written cultures together to enhance a wider human vision in matters bordering on the intellectual configuration of our human society.